Hypothalamic kappa opioid receptor mediates both diet‐induced and melanin concentrating hormone–induced liver damage through inflammation and endoplasmic reticulum stress. Issue 4 (9th August 2016) - Imbernon, Monica; Sanchez‐Rebordelo, Estrella; Romero‐Picó, Amparo; Kalló, Imre; Chee, Melissa J.; Porteiro, Begoña; Al‐Massadi, Omar; Contreras, Cristina; Fernø, Johan; Senra, Ana; Gallego, Rosalia; Folgueira, Cintia; et al.
Abstract : The opioid system is widely known to modulate the brain reward system and thus affect the behavior of humans and other animals, including feeding. We hypothesized that the hypothalamic opioid system might also control energy metabolism in peripheral tissues. Mice lacking the kappa opioid receptor (κOR) and adenoviral vectors overexpressing or silencing κOR were stereotaxically delivered in the lateral hypothalamic area (LHA) of rats. Vagal denervation was performed to assess its effect on liver metabolism. Endoplasmic reticulum (ER) stress was inhibited by pharmacological (tauroursodeoxycholic acid) and genetic (overexpression of the chaperone glucose‐regulated protein 78 kDa) approaches. The peripheral effects on lipid metabolism were assessed by histological techniques and western blot. We show that in the LHA κOR directly controls hepatic lipid metabolism through the parasympathetic nervous system, independent of changes in food intake and body weight. κOR colocalizes with melanin concentrating hormone receptor 1 (MCH‐R1) in the LHA, and genetic disruption of κOR reduced melanin concentrating hormone–induced liver steatosis. The functional relevance of these findings was given by the fact that silencing of κOR in the LHA attenuated both methionine choline–deficient, diet‐induced and choline‐deficient, high‐fat diet–induced ER stress, inflammation, steatohepatitis, and fibrosis, whereas overexpression of κOR in this area promoted liver steatosis. Overexpression of glucose‐regulated protein 78 kDa in the liver abolished hypothalamic κOR‐induced steatosis by reducing hepatic ER stress. Conclusions : This study reveals a novel hypothalamic–parasympathetic circuit modulating hepatic function through inflammation and ER stress independent of changes in food intake or body weight; these findings might have implications for the clinical use of opioid receptor antagonists. (Hepatology 2016;64:1086‐1104)